Puutarhayritysten kirjanpito - Knaapinen, Petri (Maatalouden taloudellinen tutkimuslaitos, 1998)
EU:n jäsenyys velvoitti Suomen järjestämään myös puutarhatalouden kannattavuuden seurannan osaksi unionin yhteistä FADN-kirjanpitojärjestelmää. Ensimmäiset tulokset puutarhayritysten kannattavuudesta ovat vuodelta 1996. Mukana on tavoitteena olevasta 150 yrityksestä 88 yritystä. Tulokset kattavat kasvihuoneviljelystä vihannestuotannon sekä koristekasvien tuotannon sekä avomaan viljelystä mansikan ja herukan tuotannon. Avomaan vihannesviljelystä tuloksia saadaan vasta vuodesta 1997. Kasvihuoneyritysten tulosta voi kokonaisuutena pitää verraten hyvänä. Yritysten välillä on kuitenkin suuria eroja. Parhaiten näyttävät menestyneen pakkaamo- ja markkinointiyhteistyössä kiinteästi mukana olevat yritykset. Ruukkukukkia tuottavien yritysten tulos oli myös hyvä. Parhaat kannattavuuden tunnusluvut näyttävät olevan kasvihuoneyrityksillä, joissa saadaan myös korkeimmat tuotot neliömetrialaa kohti. Marjojen tuotantoa harjoittavien yritysten tulos oli verraten heikko. Ainakin osaksi tämä johtuu siitä, että aineistossa mukana olevilla tiloilla nuorten, vielä vähätuottoisten kasvustojen osuus oli suuri ja tuotannon laajentuminen käynnissä.

The purpose of the study was to start up the compilation of bookkeeping data on horticulture as well as to test new methods for compiling the data and preparing the profitability calculations. Bookkeeping data is collected from 150 horticulture enterprises, which also constitute the sample for the FADN (Farm Accountancy Data Network) bookkeeping data delivered to the EU Commission. In the study inventory data concerning the fixed assets of the enterprises concerned were collected, and the depreciations made for taxation purposes in the result calculation were corrected by these. The bookkeeping data on horticulture contains the data on altogether 88 enterprises from 1996, including 70 enterprises practising greenhouse production and 18 engaged in the production of berries in the open. In the result calculation the data on greenhouse production were weighted according to the production lines as well as size classes in the FADN system. In addition, results of enterprises practising greenhouse production were examined as sample averages for the part of the five main production lines. Sample averages were calculated from the data on berry production for the part of enterprises specializing in the production of strawberries and currants. In the data on greenhouse production it is notable that the profitability is clearly above the average in enterprises practising the production of potted plants as well as in tomato enterprises with cooperation in packaging. In the light of the data the production of berries was quite unprofitable in 1996, which is partly due to the considerable increase in the area under berries in 1995 and 1996.
Economic results of horticulture enterprises
Keywords: Ma; FADN; puutarhayrittäjät; kirjanpito; kannattavuus; bookkeeping; profitability; horticulture economics; FADN